Rapid scalable plasma processing of thin-film Li–La–Zr–O solid-state electrolytes - Crane, Gabriel Badillo; Colburn, Thomas W.; Holmes, Sarah E.; Just, Justus ; 0000-0003-1725-1677; Cui, Yi; Dauskardt, Reinhold H. (Matter, 2025)
Solid-state electrolytes, such as lithium lanthanum zirconium oxide (LLZO), show promise as technologies for next-generation high-energy-density batteries, but commercial development has been hindered by a lack of scalable processing methods. Current fabrication methods are costly or require long annealing steps to create dense films. We report an atmospheric pressure blown-arc nitrogen plasma jet process to rapidly form sub-micrometer-thick, dense amorphous LLZO (a-LLZO) films from sol-gel precursors. Films are processed in less than 2 min, an order of magnitude faster than what has previously been reported. We demonstrate 500-nm-thick a-LLZO films processed at 350°C with an ionic conductivity of 2 × 10−6 S/cm at 30°C and 2 × 10−3 S/cm at 100°C and a conductance of 19 S at 100°C, the highest conductance of any LLZO phase to date. The films exhibit outstanding smooth surface morphology with low defectivity, advancing atmospheric plasma processing as a scalable processing method for solid-state electrolytes.
Keywords: a-LLZO; amorphous electrolytes; EXAFS; LLZO; plasma curing; scalable manufacturing; separator films; solid-state batteries; thin film; XANES